The Ideology of Kokugo : Nationalizing Language in Modern Japan - Yi, Yŏn-suk, 1956- (Book collections on Project MUSE., 2010)
This work looks at the history and ideology behind the construction of kokugo (national language). This book discusses the contributions of Ueda Kazutoshi (1867-1937) and Hoshina Koichi (1872-1955) in the creation of kokugo and moves us one step closer to understanding how the ideology of kokugo cast a spell over linguistic identity in modern Japan.